Programming phenomenology: proof of concept on adaptivity - Marcondes, Francisco S. (2018)
Phenomenology is the empirical study of mind and consciousness. Considering programming activity as a cognitive procedure, phenomenology may be applied to address some of its issues. A particular issue of interest is how one programming approach differs from others, i.e. the cognition performed when using an approach differs from the one performed using another? If they are similar the two approaches are like to be the same, otherwise essentially different. Since adaptive computing proposal is Turing-equivalent it may be discussed about the actual differences among those approaches. As an example, λ-calculus is also Turing-equivalent but since the cognition performed is different it justifies the several λ-based existing approaches. In order to accomplish such analysis, bergsonism will be used as phenomenological method to be applied in particular adaptive structure called adaptive-graph. As a result it will be argued cognition performed using adaptive-graph is different from the one performed when using non-adaptive one. Then it will generalized suggesting adaptive computing cognition shall be further explored.